Electromagnetic Feature Study of a Novel Dual-Stator Five-Phase Spoke-Type Permanent Magnet Motor for Electric Vehicles Application - Kumar R.R.; Chetri C.; Devi P.; Kumari A.; Kumar K.; Saket R.K. (My University, 2025)
The electromagnetic feature investigation of a Novel Dual-Stator Five-Phase Spoke-Type Permanent Magnet Motor (NDSFPST-PMM) for application in electric vehicles has been discussed in this paper. For this application, several features such as high fault tolerance (HFT) ability, high power-density (HPD) and high reliability are preferred in the motor. The availability of two stators in the motor ensures high power-density, whereas HFT and reliability is due to the 2-sets of five-phase armature windings. For the efficient and cost-effective use of magnets, single set of magnets are used for both the inner and outer stator-rotor system. Due to this specific arrangement, the rotor of the PMM becomes robust and light in weight. For the analysis of the PMM model, the Finite Element Method (FEM) is adopted as it gives accurate results. Further, results such as the generated back electromotive force (BEMF), torque versus current plot, torque and power versus speed plot, efficiency versus load current plot, etc. are studied for the PMM. © 2021 IEEE.